TRPC5-eNOS Axis Negatively Regulates ATP-Induced Cardiomyocyte Hypertrophy - Sunggip, Caroline; Shimoda, Kakeru; Oda, Sayaka; Tanaka, Tomohiro; Nishiyama, Kazuhiro; Mangmool, Supachoke; Nishimura, Akiyuki; Numaga-Tomita, Takuro; Nishida, Motohiro (Frontiers in Pharmacology, 2018)
Cardiac hypertrophy, induced by neurohumoral factors, including angiotensin II and endothelin-1, is a major predisposing factor for heart failure. These ligands can induce hypertrophic growth of neonatal rat cardiomyocytes (NRCMs) mainly through Ca2+-dependent calcineurin/nuclear factor of activated T cell (NFAT) signaling pathways activated by diacylglycerol-activated transient receptor potential canonical 3 and 6 (TRPC3/6) heteromultimer channels. Although extracellular nucleotide, adenosine 5'-triphosphate (ATP), is also known as most potent Ca2+-mobilizing ligand that acts on purinergic receptors, ATP never induces cardiomyocyte hypertrophy. Here we show that ATP-induced production of nitric oxide (NO) negatively regulates hypertrophic signaling mediated by TRPC3/6 channels in NRCMs. Pharmacological inhibition of NO synthase (NOS) potentiated ATP-induced increases in NFAT activity, protein synthesis, and transcriptional activity of brain natriuretic peptide. ATP significantly increased NO production and protein kinase G (PKG) activity compared to angiotensin II and endothelin-1. We found that ATP-induced Ca2+ signaling requires inositol 1,4,5-trisphosphate (IP3) receptor activation. Interestingly, inhibition of TRPC5, but not TRPC6 attenuated ATP-induced activation of Ca2+/NFAT-dependent signaling. As inhibition of TRPC5 attenuates ATP-stimulated NOS activation, these results suggest that NO-cGMP-PKG axis activated by IP3-mediated TRPC5 channels underlies negative regulation of TRPC3/6-dependent hypertrophic signaling induced by ATP stimulation.